DAYAH AND MEUNASAH IN ACEH: REFORM IN LOCAL CONTEXT - Moch. Khafidz Fuad Raya (Jurnal Tatsqif, 2021)
The history of Islamic education in the early 20th century led to various changes, especially the emergence of madrasas as an Islamic schooling system. Traditional Islamic educational institutions inevitably have to harmonise and open themselves to transformation, even though they initially experienced opposition. Using a qualitative approach with a narrative documentation method based on historical texts and observations in several Islamic educational institutions in Aceh, this article focuses on revealing the history of the dayah and meunasah as a traditional Acehnese Islamic educational institution that underwent some fundamental changes. The results found: First, the existence of the dayah is more long-term than the meunasah even though both forms of this institution are rooted in the same ideological principles with different patterns, seen from the early 20th century until implementing sharia law in Aceh after the Helsinki peace agreement, the dayah was still existed by maintaining its institutional form. Second, the emergence of madrasas as a formation of the government’s political policy on the social conditions of the people that occurred has provided space for traditional Islamic educational institutions (such as the dayah) to open themselves to including general subjects, although this second result has led to struggles; Third, there is a contestation between dayah, Islamic schools, and madrasas, with public schools driven by traditionalist and modernist groups in maintaining their existence. The contest has opened the history of the dayah and meunasah into the form of public schools and madrasas in the future, both of which apply Islamic religious material, where public schools are superior to madrasas in terms of curriculum, educational programs, and human resources.